Comparing meat abstainers with avid meat eaters and committed meat reducers - Verain, Muriel C. D.; Dagevos, Hans (Frontiers in Nutrition, 2022)
Shifting our eating patterns towards less animal-based and more plant-based diets is urgently needed to counter climate change, address public health issues and protect animal welfare. Although most consumers agree that these are important topics, many consumers are not particularly willing to decrease the meat intensity of their diets. In supporting consumers to shift their diets, it is important to understand consumers’ attitudes, motivations and preferences related to meat consumption and to take differences across consumers on these aspects into account. This study aims to in-depth research meat abstainers (vegetarians and vegans), and to explore how and to what extent they differ from avid meat eaters and committed meat reducers in terms of their 1) socio-demographic characteristics, 2) attitudes and norms, 3) food choice motives, and 4) food preferences and behavior. A survey has been conducted among a representative sample of Dutch adults. Comparisons show that meat abstainers (N=198) differ from committed meat reducers (N=171) and avid meat eaters (N=344) on the four included categories of variables. In terms of demographics, we largely confirm the stereotype of vegans and vegetarians being highly educated females. In attitudes and norms, large differences exist with meat abstainers being least pro-meat and avid meat eaters being most pro-meat. Food choice motives confirm this, with meat abstainers valuing animal welfare and a good feeling higher than committed meat reducers and avid meat eaters. Finally, differences across the groups are most pronounced in terms of their food preferences and consumption, with a much higher appreciation of plant-based protein sources among meat abstainers, a high appreciation of non-meat animal-based proteins across committed meat reducers and a high appreciation of meat products among avid meat eaters. This shows that although differences across the groups are gradual and expected, in terms of reduction motivations and preferences of protein sources the three groups (frequent meat consumption-meat reduction-meat avoidance) are very distinct, which makes it unlikely to expect big shifts from one group to another in the short term.